The Effectiveness of Propranolol in Managing Hemorrhagic Choroidal and Exudative Retinal Detachment following Ahmed Glaucoma Valve Implantation in Sturge-Weber Syndrome: Case Report and Literature Review - Raid Alhayaza (Karger Publishers, 2021)
Sturge-Weber syndrome (SWS) is a congenital neurological disorder that is characterized by hamartomas involving the skin, brain, and eyes and marked by the presence of the facial port-wine stain, which consequently leads to various ocular complications. Among all ocular comorbidities, glaucoma is the most frequently witnessed in SWS patients with a prevalence of 30%–70%. If glaucoma is refractory to conventional medical management, surgical intervention can be considered. Common complications of glaucoma procedures in SWS are choroidal detachment and suprachoroidal hemorrhage. Moreover, we report a 6-year-old girl, known case of unilateral congenital glaucoma secondary to SWS. Despite being on maximal antiglaucoma drops and undergoing multiple surgical interventions, the patient had uncontrolled intraocular pressure of her right eye. A decision to proceed with Ahmed glaucoma valve implantation (AGVI) to the right eye was made. In the immediate postoperative period, the patient developed hemorrhagic choroidal detachment and exudative retinal detachment. A trial of oral propranolol (1.5–2 mg/kg/day) was then initiated for 4 months. After 30 days from oral propranolol course initiation, we started noticing a significant improvement of the hemorrhagic choroidal and exudative retinal detachment. Spontaneously, a marked reduction in subretinal fluid and suprachoroidal hemorrhage was also seen. Thus, the improvement was correlated with the propranolol therapy. Here, we report a significant improvement of the postoperative complications of AGVI in a patient with SWS, following 4 months of oral propranolol course (1.5–2 mg/kg/day). Further studies are needed to determine the dosage, duration, and optimal mechanism by which propranolol works in this situation.